The Effect of Special Exercises Using A Ball With A Heavier Weight On The Accuracy of Scoring In Soccer Players Aged (14 – 16 Years Old) - Kadhim, Abedulrazaaq; Jassim, Ahmed (Journal of Physical Education, 2017)
The problem of the research lies in weakness in scoring specially clubs of ministry of youth and sports. The importance of the research lies in finding a tool that can be added to soccer special exercises of scoring and that was a ball with different weights. New 500gm balls were manufactures according to the official laws of the games. The researcher used the experimental method. The subjects were (14) soccer players from Montada Shebab Al Baya soccer club/ ministry of youth and sport. The subjects were dived into two groups controlling and experimental. The results showed that the special exercises and the heavier ball designed by the researcher have a positive effect in developing the accuracy of scoring more than the official ball